Opinions, actions and emotions: does the content of lies affect their detectability?. Issue 10 (25th November 2020) - Duran, Geoffrey; Dochez, Sara; Tapiero, Isabelle; Michael, George A.
ABSTRACT: People principally deceive others about opinions, actions and emotions. In two Experiments, this study examined the ability to detect these three types of lies. In Experiment 1, participants had to judge whether actors (50% females and 50% males) were telling the truth (50%) or lying (50%), whereas in Experiment 2, another sample of participants was asked to evaluate how convincing the statements were using a rating scale. One third of the statements were about activities and locations, 1/3 were opinions related to a topic of debate, and 1/3 described emotions experienced during an emotionally charged event. Results of both experiments showed that lies about opinions and emotions were detected better than lies about actions and that they were detected above chance level, unlike lies about actions. Furthermore, the truth bias was observed only in judgments about opinions and actions. Accordingly, Experiment 2 showed that lies about actions were rated as being more convincing than lies about opinions and emotions. Experiment 2 also showed that the difference between opinions, actions and emotions in lie detection was mostly due to participants' level of empathy, while empathy and subclinical psychopathy seemed to explain the differences in truth bias. The possible reasons why the three types of content are dissociated are discussed.